Exosomal miRNAs: Biological Properties and Therapeutic Potential - Hu, Guoku; Drescher, Kristen M.; Chen, Xianming (Frontiers in Genetics, 2012)
MicroRNAs (miRNAs), small non-coding regulatory RNAs that regulate gene expression at the post-transcriptional level, are master regulators of a wide array of cellular processes. Altered miRNA expression could be a determinant of disease development and/or progression and manipulation of miRNA expression represents a potential avenue of therapy. Exosomes are cell-derived extracellular vesicles that promote cell-cell communication and immunoregulatory functions. These ‘bioactive vesicles’ shuttle various molecules, including miRNAs, to recipient cells. Inappropriate release of miRNAs from exosomes may cause significant alterations in biological pathways that affect disease development, supporting the concept that miRNA-containing exosomes could serve as targeted therapies for particular diseases. This review briefly summarizes recent advances in the biology, function, and therapeutic potential of exosomal miRNAs.